Satellite-Based Analysis of Spatial–Temporal Distributions of NH3 and Factors of Influence in North China - Zhi-li, Deng; Qian-qian, Zhang; Xing-ying, Zhang (Frontiers in Environmental Science, 2021)
NH3 is an important part of the global nitrogen cycle as the most important atmospheric alkaline gas. NH3 reacts rapidly with acidic substances and accelerates the generation of particulate matter (PM2.5), which has important effects on the atmosphere and climate change. In this study, satellite NH3 column data were used to analyze spatial and temporal distributions of NH3 in China, and because of high concentrations and rates of change, North China was selected for more detailed analysis. Qualitative analysis was conducted to understand the relations between concentrations of NH3 and those of SO2 and NO2. Last, the random forest method was used to quantify relations between concentrations of atmospheric NH3 and factors influencing those concentrations, such as meteorological factors, NH3 self-emission, and concentrations of SO2 and NO2. Satellite-retrieved NH3 column concentrations showed an increasing trend during the 11 years from 2008 to 2018, and the rate of increase in summer was faster than that in winter. In those 11 years, NH3 self-emission had the greatest influence on NH3 concentrations. Concentrations of SO2 and NO2 had some effect and were negatively correlated with NH3 concentrations. The effect of SO2 on NH3 concentration was greater than that of NO2. Atmospheric NH3 concentration was also affected by meteorological conditions (temperature, relative humidity, pressure, and wind). In summer, temperature is the most important factors of meteorological conditions and relative humidity is the most important factors in winter. Therefore, to better control atmospheric NH3 concentrations, it is particularly important to formulate practical NH3 emission reduction policies and to consider the effects of SO2 and NO2 emission reduction policies.